Identification of lectin receptors for conserved SARS‐CoV‐2 glycosylation sites. (23rd August 2021) - Hoffmann, David; Mereiter, Stefan; Jin Oh, Yoo; Monteil, Vanessa; Elder, Elizabeth; Zhu, Rong; Canena, Daniel; Hain, Lisa; Laurent, Elisabeth; Grünwald‐Gruber, Clemens; Klausberger, Miriam; Jonsson, Gustav; et al.
Abstract: New SARS‐CoV‐2 variants are continuously emerging with critical implications for therapies or vaccinations. The 22 N ‐glycan sites of Spike remain highly conserved among SARS‐CoV‐2 variants, opening an avenue for robust therapeutic intervention. Here we used a comprehensive library of mammalian carbohydrate‐binding proteins (lectins) to probe critical sugar residues on the full‐length trimeric Spike and the receptor binding domain (RBD) of SARS‐CoV‐2. Two lectins, Clec4g and CD209c, were identified to strongly bind to Spike. Clec4g and CD209c binding to Spike was dissected and visualized in real time and at single‐molecule resolution using atomic force microscopy. 3D modelling showed that both lectins can bind to a glycan within the RBD‐ACE2 interface and thus interferes with Spike binding to cell surfaces. Importantly, Clec4g and CD209c significantly reduced SARS‐CoV‐2 infections. These data report the first extensive map and 3D structural modelling of lectin‐Spike interactions and uncovers candidate receptors involved in Spike binding and SARS‐CoV‐2 infections. The capacity of CLEC4G and mCD209c lectins to block SARS‐CoV‐2 viral entry holds promise for pan‐variant therapeutic interventions. SYNOPSIS: SARS‐CoV‐2 Spike harbors 22 conserved N ‐glycan sites. Here we report the first extensive map of lectin‐Spike interactions and assess the Spike‐lectins associations at single molecule resolution. A lectin library screen identified Clec4g and CD209c to bind the SARS‐CoV‐2 spike protein. The lectin‐spike interaction was visualized and quantified using atomic force microscopy. A binding site of CLEC4G is located within the RBD‐ACE2 interface. The identified lectins block SARS‐CoV‐2 viral entry. Abstract : The lectin receptors Clec4g and CD209c bind to the glycosylated SARS‐CoV‐2 Spike protein to interfere with Spike binding to cell surfaces and SARS‐CoV‐2 infection.